2009
DOI: 10.1016/j.pscychresns.2009.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Altered white matter microstructure in adolescent substance users

Abstract: Chronic marijuana use during adolescence is frequently comorbid with heavy alcohol consumption and associated with CNS alterations, yet the influence of early cannabis and alcohol use on microstructural white matter integrity is unclear. Building on evidence that cannabinoid receptors are present in myelin precursors and affect glial cell processing, and that excessive ethanol exposure is associated with persistently impaired myelination, we used diffusion tensor imaging (DTI) to characterize white matter inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
163
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 161 publications
(179 citation statements)
references
References 104 publications
12
163
2
2
Order By: Relevance
“…Wilson et al [37] reported that the onset of cannabis use in adolescence was associated with a reduction in the gray matter percentage and an increase in the white matter percentage after normalization by the total intracranial volume. The volumetric change in white matter is consistent with alterations in the integrity and structure of several of its bundles, including changes in the fractional anisotropy and mean diffusivity of the corpus callosum [38], fronto-parietal [39] and fronto-temporal circuits [40].…”
Section: Neurocognitive Effects Of Cannabis Usesupporting
confidence: 56%
“…Wilson et al [37] reported that the onset of cannabis use in adolescence was associated with a reduction in the gray matter percentage and an increase in the white matter percentage after normalization by the total intracranial volume. The volumetric change in white matter is consistent with alterations in the integrity and structure of several of its bundles, including changes in the fractional anisotropy and mean diffusivity of the corpus callosum [38], fronto-parietal [39] and fronto-temporal circuits [40].…”
Section: Neurocognitive Effects Of Cannabis Usesupporting
confidence: 56%
“…Early onset cannabis users (before age 17) have been found to have smaller whole brain volumes, lower percent cortical grey matter, higher percent white matter and increased cerebral blood flow compared to later onset users (Wilson et al 2000). Altered cortical gyrification in the frontal lobe and abnormal age-related changes to gyrification and cortical thickness have recently been reported in adolescent and young adult users (Mata et al 2010), and further studies of young adult (Arnone et al 2008;Allin et al 2009) and adolescent (Ashtari et al 2009;Bava et al 2009; press) cannabis users have provided evidence for pathology in the corpus callosum and various fronto-temporal, occipito-frontal and posterior connections that develop during adolescence. It is suggested that cannabis use during adolescence may affect the trajectory of normal brain maturation resulting in white matter aberrations, which may underlie compromised cognitive processing.…”
Section: Discussionmentioning
confidence: 94%
“…Subtle neural architectural changes may be occurring over the abstinence period, and the acute impact on neural development may not be fully captured at baseline for this predictor. Neural recovery is likely to extend past 28 days and well into the year following cessation of use, as residual effects of marijuana use have been reported in cognitive and neuroimaging markers from days to months following cessation of use (Ashtari et al, 2011;Bava et al, 2009;Matochik et al, 2005;Medina et al, 2007;Meier et al, 2012;Pope et al, 2001;Schweinsburg et al, 2008;Tapert et al, 2007). Pre-existing structural differences are also likely to contribute, as smaller orbitofrontal cortex volume predicted initiation of cannabis use by age 16 (Cheetham et al, 2012).…”
Section: Discussionmentioning
confidence: 99%